Pricing Payment Cards - Özlem Bedre-Defolie; Emilio Calvano (European School of Management and Technology (ESMT), 2010)
Payment card networks, such as Visa, require merchants' banks to pay substantial 'interchange' fees to cardholders' banks, on a per transaction basis. This paper shows that a network's profit-maximizing fee induces an inefficient price structure, over-subsidizing card usage and over-taxing merchants. In contrast to the literature we show that this distortion is systematic and arises from the fact that consumers make two distinct decisions (membership and usage) whereas merchants make only one (membership). These findings are robust to competition for cardholders and/or for merchants, network competition, and strategic card acceptance to attract consumers.
urn:nbn:de:101:1-201106143691
Keywords: G21; L11; L42; L31; L51; K21; 650; payment card networks; interchange fees; merchant fees; Kreditkartengesellschaft; Gebühr; Anreizregulierung; Wohlfahrtsanalyse; Unvollkommener Wettbewerb; Theorie